Exome Sequencing Identifies a Novel Sorting Nexin 14 Gene Mutation Causing Cerebellar Atrophy and Intellectual Disability. (24th October 2018) - Al-Hashmi, Nadia; Mohammed, Mohammed; Al-Kathir, Salim; Al-Yarubi, Naeema; Scott, Patrick
Abstract : The autosomal recessive cerebellar ataxias (ARCA) affect both the central and the peripheral nervous systems. They are also characterized by a relatively high level of genetic heterogeneity with well over 40 genes already implicated. The present study aimed to identify the gene mutation responsible for a complex phenotype comprising cerebellar ataxia and intellectual disability segregating in an Omani consanguineous family. Homozygosity-guided exome data analysis identified a novel frameshift mutation (c.2319_2322del) within the sorting nexin 14 gene (SNX14), which predicts complete absence of the SNX14 encoded protein. Segregation within the family of the sequence variation is consistent with its pathogenic role. Importantly, loss-of-function mutations in SNX14 have recently been described as a cause of a clinically distinguishable recessive syndrome consisting of cerebellar atrophy, ataxia, coarsened facial features, and intellectual disability. This study expands the genetic diversity of ataxia genes in the Omani population and have important implications for the clinical and molecular diagnosis of this condition in affected individuals.